Toxicity Associated with Immune Checkpoint Inhibitors: Analysis of Immune-Related Adverse Events with a Pembrolizumab Biosimilar (Pembroria) - Fedyanin, M. Yu; Snegovoy, A. V.; Breder, V. V.; Linkova, Yu. N.; Zinkina-Orikhan, A. V.; Setkina, S. B.; Fogt, S. N.; Chistiakov, V. S.; Kravtsova, N. A. (Bezopasnostʹ i risk farmakoterapii (Online), 2023)
In recent years, there has been a significant increase in the number of patients with malignancies treated with immune checkpoint inhibitors (ICIs), including the anti-programmed cell death protein 1 (anti–PD-1) agent pembrolizumab. One of the important aspects of conducting clinical trials with ICIs is the assessment of the risk of developing immune-related adverse events (irAEs). The aim of the study was to evaluate the safety of a pembrolizumab biosimilar (BCD-201, Pembroria) compared with a reference medicinal product using the results of a phase I clinical trial and the available medical literature. Materials and methods. A phase I double-blind, randomised, controlled clinical trial (BCD-201-1) has been conducted in patients with advanced melanoma and non-small-cell lung cancer (n=131). Patients were randomly allocated in a 1:1 ratio to receive either BCD-201 (Pembroria) or the reference medicinal product (Keytruda®), administered intravenously at a dose of 200 mg every 3 weeks for up to 24 weeks or until disease progression or unacceptable toxicity is observed. Since the trial results remain blinded at the time of this writing, treatment group data are masked. Results. The study demonstrated the equivalence of pharmacokinetics and comparable safety profiles of pembrolizumab biosimilar and reference medicinal products. Both medicinal products were well tolerated; the frequency of all-grade irAEs was comparable between treatment groups (21.2% in Group 1 vs 21.5% in Group 2). Most irAEs were mild to moderate, with the exception of a case of Grade 3 diarrhoea and immune-mediated enterocolitis in one study subject; there were no statistically significant differences in the median time to development of irAEs between treatment groups (Р=0.22, two-sided Wilcoxon test). Conclusions. The analysed period of the BCD-201-1 trial demonstrated comparable safety characteristics of Pembroria and Keytruda®, which is consistent with the published safety data on the latter. Information on the similarity of long-term safety profiles of the pembrolizumab biosimilar and the reference medicinal product will be obtained from ongoing clinical trials.